Pengembangan Media Pembelajaran Fisika Berbasis Sparkol Videoscribe dan AVS Video Editor Untuk Siswa Kelas X SMK Mahadhika 2 Jakarta Timur - Siti Rubiyah; Dasmo Dasmo; Huri Suhendri (UNIVERSITAS INDRAPRASTA PGRI, 2020)
In the implementation of this research, input and consideration can be made for all parties involved in the world of education, especially in physics lessons. This type of research is development research (Research and Development). The results of the research and discussion can be concluded that the development of learning media for physics-based on Sparkol Videoscribe and AVS Video Editor has a good category. The feasibility of physics learning media based on Sparkol Videoscribe and AVS Video Editor for physics subject matter of straight motion with constant velocity and acceleration is in the good category with the final percentage is 82.93%. So that the media can be used in learning because it is considered valid and worthy of being used as media that support learning in the classroom. This learning media increases students' interest, motivation, and concentration in learning physics in class. Schools should provide support in the form of facilities and infrastructure that can support teaching and learning activities.So that students get maximum service in teaching and learning activities.